1 упростите выражение (5√5+√45)-√5(2√2-√50)*√2 (2) сократите дробь √ав- √ас\5√в-5√с (3)освободите знаменатель от иррацианальности 12 \√11 +√5
1 упростите выражение (5√5+√45)-√5(2√2-√50)*√2 (2) сократите дробь √ав- √ас\5√в-5√с (3)освободите знаменатель от иррацианальности 12 \√11 +√5
Ответ(ы) на вопрос:
3)12/(sqrt(11)+sqrt(5))=12(sqrt(11)-sqrt(5))/16 <-- ответ
2)(sqrt(ab)-sqrt(ac))/(5sqrt(b)-5sqrt(c))=(sqrt(a)*(sqrt(b)-sqrt(c))/(5*(sqrt(b)-sqrt(c))=
sqrt(a)/5 НО b не равно с
1)sqrt(45)=3*sqrt(5)
(5sqrt(5)+sqrt(45))-sqrt(5)*(4-sqrt(50)*sqrt(2))=8*sqrt(5)-sqrt(5)*(-6)=14sqrt(5)
sqrt квадратный корень
Не нашли ответ?
Похожие вопросы